The determinants of corporate cash management policies: Evidence from around the world - Kusnadi, Yuanto; Wei, K.C. John (Journal of Corporate Finance, 2011)
We examine the determinants of corporate cash management policies across a broad sample of international firms. We document that firms in countries with strong legal protection of minority investors are more likely to decrease their cash holdings in response to an increase in cash flow than are firms in countries with weak legal protection. This relationship is most pronounced for firms that are financially constrained and those with high hedging needs. More importantly, we do not find evidence that financial development plays an incremental impact on the cash flow sensitivity of cash, after controlling for the effect of legal protection. Therefore, we argue that the legal protection of investors (rather than financial development) represents the first-order effect in influencing international firms' cash management policies. The results are robust to alternative specifications. In general, our findings reinforce the importance of country-level legal protection of investors in mitigating the effects of firm-level financial constraints and hedging needs on corporate cash management policies.